MANAJEMEN PROGRAM TAHFIZH UNTUK MENINGKATKAN KEUNGGULAN HAFALAN QUR’AN PESERTA DIDIK DENGAN METODE WAFA DI SMP IT INSAN MADANI, KOTA PALOPO - Wulandari, Dewi Suci (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research is intended to raise facts, circumstances, variables, and phenomena that occur in Tahfizh Program Management. The results of this study indicate that, 1). Tahfizh program management 2). The Qur'an memorization method implies that students can memorize according to the target and students become disciplined in time in everything, the ability to memorize students is increasing, students become more enthusiastic about memorizing Qur'anic verses without seeing the Qur'an (bil ghoib). 3) The obstacles are health, laziness, impatience and despair, time management, blindness to makhrajul letters, similarity of verses, and places to memorize verses. The solution is to memorize based on sincerity, enthusiasm, motivation from the scope of school and family and always istiqomah in achieving the target of memorizing the Qur'an